Quantification methods for human and large animal leukocytes using DNA dyes by flow cytometry. Issue 6 (6th June 2016) - Pieper, Ina Laura; Radley, Gemma; Chan, Chris H. H.; Friedmann, Yasmin; Foster, Graham; Thornton, Catherine A.
Abstract: Ovine and bovine blood is used heavily within the development of blood‐handling medical devices, such as heart pumps (left ventricular assist devices, LVADs), for which blood cell damage needs to be monitored during in vitro testing. Hematology analyzers provide cell counts but no information about cell viability. The anthraquinone DNA dyes CyTRAK Orange™ and DRAQ7™ have practical and spectral properties rendering them suitable for multicolor assays. Compared to other DNA dyes such as Vybrant Dyecycle, CyTRAK Orange enables a faster staining protocol and does not require incubation at +37°C. Compared to traditional viability dyes such as propidium iodide and 7AAD, DRAQ7's unique spectral profile of excitation in both blue and red lasers and far‐red emission enables identification of dual positive dead cell events and frees up detectors for use with other reagents. CyTRAK Orange and DRAQ7 could be used in combination with absolute counting bead standards to provide cell counts and viability but the combination of these dyes has previously only been used for microscopy on rodent cells. The purpose of this study was to evaluate the use of these dyes in combination in large animal blood samples for flow cytometry. A viability and cell counting protocol for bovine, ovine, and human leukocytes using CyTRAK Orange and DRAQ7 was prepared. Four different counting bead standards were evaluated using the Navios and FACSAria cytometers and compared to counts obtained from hematology analyzers. CyTRAK Orange successfully detected CD45 + leukocytes in all species. The DRAQ7 single‐stained dead cell counts correlated well with the CyTRAK Orange/DRAQ7 double‐stained dead cell counts in human and bovine blood, but not in ovine blood, which could be related to the blood source. In conclusion, for human and bovine blood, this method works well for viability counts using different flow cytometers and bead standards. © 2016 International Society for Advancement of Cytometry